2018
DOI: 10.1021/acsomega.8b00825
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/Nickel Oxide-Based Nanocomposite of Polyaniline with Special Reference to Ammonia Sensing

Abstract: Polyaniline@graphene/nickel oxide (Pani@GN/NiO), polyaniline/graphene (Pani/GN), and polyaniline/nickel oxide (Pani/NiO) nanocomposites and polyaniline (Pani) were successfully synthesized and tested for ammonia sensing. Pani@GN/NiO, Pani/NiO, Pani/GN, and Pani were characterized using X-ray diffraction, UV–vis spectroscopy, Raman spectroscopy, scanning electron microscopy, and transmission electron microscopy. The as-prepared materials were studied for comparative dc electrical conductivity and the change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…The main reason for a decrease and increase in electrical conductivity is due to chemisorptions and desorption of ammonia respectively, involving the interaction between the lone pair of ammonia and positive polarons on the polypyrrole backbone. The results show that there is no chemical reaction between ammonia and polypyrrole leading to complete reversibility of electrical conductivity due to un-doping of the polymer [ 12 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for a decrease and increase in electrical conductivity is due to chemisorptions and desorption of ammonia respectively, involving the interaction between the lone pair of ammonia and positive polarons on the polypyrrole backbone. The results show that there is no chemical reaction between ammonia and polypyrrole leading to complete reversibility of electrical conductivity due to un-doping of the polymer [ 12 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Husain et al fabricated a pellet-shaped ammonia sensor utilizing polythiophene/ multi walled carbon nanotubes and polythiophene/ single walled carbon nanotubes (PTh/MWCNT and PTh/SWCNT) nanocomposites which can detect it selectively at an extremely low concentration of 0.1 and 0.5 ppm, respectively [ 16 , 17 ]. Ahmad et al reported a novel pellet-shaped ammonia sensor based on Pani/nickel oxide/graphene nanocomposites with lower detection limit of 170 ppm at room temperature [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in present case no any characteristics peaks shown in above mentioned range but a broad bump observed which reveals the amorphous nature of PANI. In PANI-NiO composite the characteristics peaks appears at 2θ = 37 , 43 , 62 , and 75 , respectively, corresponding to (111), (200), (220), and (310) indices confirmed the dispersion of NiO nanoparticles in the PANI matrix 33.…”
mentioning
confidence: 70%
“…On the other hand, the sharp peaks at 2θ = 37.3° (111), 43.4° (200), 62.6° (220), 74.9° (311), and 78.7° (222) revealed the presence of face-centered core crystalline NiO (JCPDS no. 04-0835) embedded in Pbp [ 44 , 45 , 46 ]. The appearance of characteristic diffraction peaks in the Pbp@NiO 0.2 suggests that NiO is embedded in the Pbp host matrix and yet maintains a high degree of crystallinity.…”
Section: Resultsmentioning
confidence: 99%